Spirituality, self-care, and social activity in the primary medical care of elderly patients: results of a cluster-randomized interventional trial (HoPES3) - Sturm, Noemi; Krisam, Johannes; Szecsenyi, Joachim; Bentner, Martina; Frick, Eckhard; Mächler, Ruth; Schalhorn, Friederike; Stolz, Regina; Valentini, Jan; Joos, Stefanie; Straßner, Cornelia (Deutsches Ärzteblatt, 2022)
Self-efficacy is decisive for the quality of life of elderly, multimorbid persons. It may be possible to strengthen patients’ self-efficacy can be strengthened by the targeted reinforcement of individual spirituality, social activity, and self-care. This hypothesis was tested with the aid of a complex intervention.